2021
DOI: 10.1007/s00262-021-02884-w
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic role of the systemic immune–inflammation index in upper tract urothelial carcinoma treated with radical nephroureterectomy: results from a large multicenter international collaboration

Abstract: Purpose To investigate the prognostic role of the preoperative systemic immune–inflammation index (SII) in patients with upper tract urothelial carcinoma (UTUC) treated with radical nephroureterectomy (RNU). Materials and methods We retrospectively analyzed our multi-institutional database to identify 2492 patients. SII was calculated as platelet count × neutrophil/lymphocyte count and evaluated at a cutoff of 485. Logistic regression analyses were perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 37 publications
1
28
0
Order By: Relevance
“…Moreover, given that high-grade URS biopsy and cytology were significantly associated with higher disease upstaging rates than low-grade biopsy and cytology, in the univariable analysis, the URS biopsy is suggestive of problems in reliability for staging high-grade UTUC. Ways to overcome the sampling issue are the use of an access sheath that allows for repeated sampling, imaging, and make for biomarkers [23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, given that high-grade URS biopsy and cytology were significantly associated with higher disease upstaging rates than low-grade biopsy and cytology, in the univariable analysis, the URS biopsy is suggestive of problems in reliability for staging high-grade UTUC. Ways to overcome the sampling issue are the use of an access sheath that allows for repeated sampling, imaging, and make for biomarkers [23][24][25][26][27] .…”
Section: Discussionmentioning
confidence: 99%
“…The combination had the largest area under the curve compared to that for SII or PNI alone and other clinical factors, indicating its advantage in predicting survival. A large multi-institutional cohort from the international UTUC collaboration study that included 2492 cases with RNU showed that altered SII was significantly associated with higher pathologic stages and worse survival outcomes [6]. Additionally, the decision curve analysis was used to evaluate the clinical benefit of SII.…”
Section: Discussionmentioning
confidence: 99%
“…During initial diagnosis, almost 60% of UTUCs were invasive, which is higher than that in UBUC [3]. Several studies have attempted to identify prognostic factors in patients with UTUC [3][4][5][6]. These models are based on age, tumor grade, pathologic tumor grade, lymph node metastasis, lymph vascular invasion, tumor multifocality, and tumor architecture [3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations